2010
DOI: 10.1016/j.febslet.2010.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Fas activation in adipocytes impairs insulin‐stimulated glucose uptake by reducing Akt

Abstract: a b s t r a c tFas (CD95) belongs to the superfamily of the tumor necrosis factor (TNF) receptors. Besides its key role in apoptosis, Fas contributes to non-apoptotic pathways such as cell proliferation and inflammation. In 3T3-L1 adipocytes, activation of Fas by Fas ligand decreased insulin-stimulated glucose uptake, without affecting cell viability. This decrease in glucose uptake was accompanied by reduced protein expression and diminished phosphorylation of Akt. Similarly, insulin-stimulated glucose incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…2 ), consistent with our earlier observation ( 11 ), and without affecting their viability as assessed by Terminal deoxynucleotidyltransferase dUTP nick end labeling assay (see supplementary Fig. I ) and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide determination ( 19 ). Fractional reesterifi cation did not decrease upon FasL incubation (basal: 68.0 ± 2.6%; 6 h FasL: 64.0 ± 6.0%; 12 h FasL: 63.6 ± 5.5%; P = 0.8).…”
Section: Fas-mediated Lipolysis Is Camkii Dependentsupporting
confidence: 91%
See 2 more Smart Citations
“…2 ), consistent with our earlier observation ( 11 ), and without affecting their viability as assessed by Terminal deoxynucleotidyltransferase dUTP nick end labeling assay (see supplementary Fig. I ) and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide determination ( 19 ). Fractional reesterifi cation did not decrease upon FasL incubation (basal: 68.0 ± 2.6%; 6 h FasL: 64.0 ± 6.0%; 12 h FasL: 63.6 ± 5.5%; P = 0.8).…”
Section: Fas-mediated Lipolysis Is Camkii Dependentsupporting
confidence: 91%
“…We recently showed that treatment of 3T3-L1 adipocytes with 2 ng/ml FasL for 12 h reduced protein levels of Akt/ PKB (protein kinase B) ( 19 ). Moreover, a recent publication reported that deletion of rictor, an essential component of the Akt kinase mammalian target of rapamycin complex 2 (mTORC2), increases basal lipolysis as well as phosphorylation of HSL at Ser563 in adipocytes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fas has also been implicated in NAFLD in people 27 , and in experimental models 28, 29 . Reduced hepatic steatosis was also observed in mice with Fas deletion specifically from adipocytes 30 . These data imply that TNF ligands may promote NAFLD pathogenesis via their cognate receptors.…”
Section: Discussionmentioning
confidence: 81%
“…Supporting the importance of apoptosis in adipose tissue inflammation, mice with a conditional deletion of a key pro-apoptotic molecule (Bid) are protected from adipocyte apoptosis, adipose tissue immune cell infiltration and insulin resistance [85]. Moreover, adipocyte specific inactivation of the death receptor Fas (CD95) improves insulin sensitivity and reduces hepatic steatosis as well as adipose tissue inflammation in high fat diet induced obese mice [86], whereas activation of Fas in adipocytes stimulates pro-inflammatory cytokine production and causes adipocyte dysfunction [87,88]. Importantly, we could translate many of the associations between Fas expression and the phenotype into the human situation [84].…”
Section: Autophagy Apoptosis and Immune Cell Infiltration In Adiposementioning
confidence: 99%